A Study of Clinical Pharmacist Initiated Changes in Drug Therapy in a Teaching Hospital - Alagiriswami, Bhupathy; Ramesh, Madhan; Parthasarathi, Gurumurthy; Basavanagowdappa, Hatthur (Indian Journal of Pharmacy Practice)
This study was aimed to assess and quantify the pharmacist-initiated changes in drug therapy and its cost savings at a tertiary care South Indian Hospital. The medication details of all patients enrolled to the study was collected prospectively and reviewed independently by the intervening pharmacist to identify any Drug Related Problems (DRPs). Where an DRP was identified, it was discussed with physician and suitable suggestion was provided. Clinical significance of each intervention was graded based on the expected clinical outcome. An independent panel consisting of clinician and academic clinical pharmacists reviewed all the interventions made by the intervening pharmacist for potential cost savings relating to length of stay, readmission, drugs, medical procedures and laboratory monitoring. A total of 261 DRPs were identified from 189 patients. The incidence of DRPs was found to be 7.9 per 100 patients. The most common DRP was found to be drug use without indication (18%) followed by improper drug selection (14%). Seventeen percent of the DRPs observed were in patients suffering from cardiovascular disorders followed by respiratory disorders (15%). The average time spent for each intervention was 12.5 minutes. The most frequent change initiated by the intervening pharmacist was cessation of the drug (20%). The annualized cost savings incurred by the pharmacist-initiated changes in drug therapy was Rs: 46,686 /=. In our study, pharmacist initiated change in drug therapy was well accepted by the physicians. The study demonstrates that routine clinical pharmacist review of in-patient drug therapy can improve patient outcome and reduce patients' healthcare cost.
Keywords: Pharmacist; Intervention; Drug therapy; Drug related problems; Cost